The Emotional and Cultural Aspects of Exotic Wallpapers in Interior Design (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article is devoted to the study of the world of exotic landscape wallpapers and their influence on interior design. The authors consider emotional and psychological aspects of wallpaper use, technological innovations in production, as well as the impact on cultural diversity and sustainable design. The article includes analyses of practical applications in various projects and raises challenges for future research.